Work readiness Generation Z's on diploma programme: The influence internship program and digital literacy - Lina Rifda Naufalin; Mintasih Indriayu; Sulistyandari Sulistyandari (Jurnal Pendidikan Vokasi, 2024)
This study aims to examine how Merdeka Belajar Kampus Merdeka (MBKM) and digital literacy affect Generation Z's work readiness for the Diploma Programme. The study involved 169 students from the Diploma Programme of the Faculty of Economics and Business, Jenderal Soedirman University, and 90 students were randomly selected as the sample because the population was homogeneous, meaning that all students had participated in MBKM internships. The data analysis used the Structural Equation Model (SEM) with the Partial Least Square (PLS) method as an alternative. The quality of the structural model was evaluated by testing the measurement index, namely R2. The test results revealed: 1) MBKM internships had a significant impact on the work readiness of generation Z, with a t-test value of 8.323 > t critical value of 1.987; 2) digital literacy did not have a significant impact on work readiness, with a t-test value of 0.744 < t critical value of 1.987; and 3) there was a simultaneous influence of MBKM internships and digital literacy on work readiness, with a Sig value of 0.000<0.05 and R2 of 0.844 indicating that MBKM internships and digital literacy jointly explained 84.4% of the variance in work readiness. Recommendations for policymakers regarding diploma programs include integrating digital literacy as a fundamental component of the curriculum across all disciplines, enhancing access to internship opportunities via industry collaborations, employing virtual internships and remote work simulations, and upgrading infrastructure while ensuring access to technology.